2006
DOI: 10.1002/bit.21150
|View full text |Cite
|
Sign up to set email alerts
|

Increased heterologous protein production by Saccharomyces cerevisiae growing on ethanol as sole carbon source

Abstract: Saccharomyces cerevisiae is a widely used host organism for the production of heterologous proteins, often cultivated in glucose-based fed-batch processes. This production system however has many factors limiting the productivity, mainly towards the end of the fermentation. For the optimised production of a Camelid antibody fragment this process was evaluated. In shake flask cultivations, it was found that ethanol has a strong effect on productivity increase and therefore glucose and ethanol fed-batch fermenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 47 publications
3
19
0
Order By: Relevance
“…The presence of ethanol in the expression medium was necessary to detect laccase activity in microcultures. Although inhibition of growth in response to increased ethanol concentrations due to changes in yeast physiology and medium redox balance has been reported (21), we found that the use of ethanol as an extra carbon source was beneficial for the heterologous production of laccase and yeast growth (62). The improved secretion of laccase in the presence of ethanol was in accordance with previous reports of laccase production in other organisms (35,37).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The presence of ethanol in the expression medium was necessary to detect laccase activity in microcultures. Although inhibition of growth in response to increased ethanol concentrations due to changes in yeast physiology and medium redox balance has been reported (21), we found that the use of ethanol as an extra carbon source was beneficial for the heterologous production of laccase and yeast growth (62). The improved secretion of laccase in the presence of ethanol was in accordance with previous reports of laccase production in other organisms (35,37).…”
Section: Discussionsupporting
confidence: 91%
“…The improved secretion of laccase in the presence of ethanol was in accordance with previous reports of laccase production in other organisms (35,37). In addition to increasing cytoplasmic membrane permeability (38,48), ethanol may generate a stress response in the cell, inducing the expression of the chaperones that are involved in the protein folding/secretion process (62). Copper uptake is essential for laccase expression (28), establishing a compromise between protein secretion and copper toxicity when choosing the final copper concentration (in our case, 2 mM CuSO 4 ).…”
Section: Discussionsupporting
confidence: 90%
“…This is at least an order of magnitude larger than the yields reported for recombinant scFv (0.3 mg/L), Fab and diabody (100 g/L) against scorpion toxins (Mousli et al, 1999;Devaux et al, 2001;Aubrey et al, 2004;Juste et al, 2007). Switching to fermentation of Nanobodies in yeasts might increase the production level even more (Van de Laar et al, 2007) allowing experiments and therapies that require vast amounts of antibodies.…”
Section: Discussionmentioning
confidence: 76%
“…Submitted) or by converting oxidized glutathione (GSSG) into reduced glytathione (GSH). GSH plays an very important role during the refolding of mis-folded proteins (Tu et al 2000), and the shortage of GSH could lead to hyper-oxidizing conditions in the ER (Van de Laar et al 2007), and produce more ROS through futile cycling of the folding process (Nguyen et al 2011). There may also be a favorable heat shock-like effect induced by ethanol (Alexandre et al 2001; Piper 1995).…”
Section: Resultsmentioning
confidence: 99%